Thermal transport and optical anisotropy in CVD grown large area few-layer MoS2 over an FTO substrate - Singh A.; Gupta R.K.; Mishra A.K. (My University, 2025)
Atomically thin MoS2 is a promising candidate for its integration into devices due to its strikingly unique electronic, optical, and thermal properties. Here, we report the fabrication of a few-layer MoS2 thin film over a conducting fluorine-doped tin oxide-coated glass substrate via a one-step chemical vapor deposition method. We have quantitatively analyzed the nonlinear temperature-dependent Raman shift using a physical model that includes thermal expansion and three- and four-phonon anharmonic effects, which exhibits that the main origin of nonlinearity in both the phonon modes primarily arises from the three-phonon anharmonic process. We have also measured the interfacial thermal conductance (g) and thermal conductivity (ks) of the synthesized film using the optothermal Raman spectroscopy technique. The obtained values of g and ks are ∼7.218 ± 0.023 MW m−2 K−1 and ∼40 ± 2 W m−1 K−1, respectively, suggesting the suitability of thermal dissipation in MoS2 based electronic and optoelectronic devices. Furthermore, we performed a polarization study using the angle resolved polarized Raman spectroscopy technique under non-resonance and resonance excitations to reveal the electron-photon-phonon interaction in the prepared MoS2, based on the semi-classical theory that includes deformation potential and Fröhlich interaction. Our study provides much needed experimental information about thermal conductivity and polarization response in a few-layer MoS2 grown over the conducting substrate, which is relevant for applications in low power thermoelectric and optoelectronic devices. © 2024 Author(s).